Aneurysm of the descending thoracic aorta presenting with paraplegia which significantly resolved following surgical repair - Aljanadi, Firas; Doyle, Joseph (International Surgery Journal, 2021)
Spinal cord infarction secondary to dissecting thoracic aortic aneurysm is a relatively rare phenomenon; it is uncommon for descending aortic aneurysm to present with paraplegia. We report the case of 60 year old man presenting with sudden onset paraplegia secondary to spinal cord infarction caused by dissecting thoracic aortic aneurysm with intraluminal thrombus. Spinal MRI confirmed findings and he underwent emergency surgery. Post-operatively he displayed neurological improvement, and was mobilising with a frame by 2-month outpatient clinic review.